Effects of crop residues for animal consumption and soil enhancement on the electricity generation potential of residues: A case study of Sawla-Tuna-Kalba district, Ghana - Awaafo, Augustine; Awafo, Edward A.; Mahdavi, Meisam; Vera, David; Akolgo, Gilbert Ayine; Amankwah, Emmanuel; Jurado, Francisco (International Journal of Agricultural and Biological Engineering, 2024)
Many studies have estimated the potential of crop residues for energy generation globally and recognized its great potential, especially in rural areas where on-grid electricity is uneconomical. However, crop residues have other equally important uses as animal feed and as mulch for soil enhancement, especially in rural farming communities. Nevertheless, most of the known studies have neglected the estimation of the quantity of crop residues that will be required for feeding animals and also for the enhancement of soil through mulching in their energy potential estimation from crop residues. Neglecting these two important uses can lead to the over-exploitation of the residues for energy generation at the expense of conservation agriculture practices as well as depriving animals of quality feed which can lead to low crop yield and animal production, with the ability to cause hunger and poverty. This study has assessed the potential of electricity generation from agricultural residues in the Sawla-Tuna-Kalba district of Ghana using gasification technology, taking cognizance of the proportion of residues needed for animal consumption and soil enhancement. The results of the study indicate that out of the 207 646.22 t of residues that can be generated from maize, yam, cassava, millet, sorghum, and groundnut, 26 830.36 t (representing 13%) will be required by sheep, goats, and cows for consumption, and 13 936.17 t (representing 7%) will be required for mulching soils where the crops are planted. Also, it was found that a total of 592.17 MW∙h of electricity can be generated from crop residues without animal consumption and soil enhancement needs, while 461.89 MW∙h could be generated from the residues, considering animal feed and soil enhancement. This study has indicated that it is not enough to consider soil enhancement and animal feeding in agricultural biomass power generation through recovery factors without the exact quantification of residues required for these purposes since this can lead to a violation of conservation agricultural practice. Hence, it is concluded that the proper estimation of residues required for soil enhancement needs and animal feeding must be considered in the estimation of crop residues available for electricity generation following the method proposed in this study. It is further concluded from this study that, the proper utilization of crop residues serve as an important resource for meeting the electricity demand of the inhabitants in the study location without compromising on the residues that will be required for the consumption of all the animals in the location as well as for enhancement of the soil. Key words: animal feed; crop residue; electricity generation; soil enhancement DOI: 10.25165/j.ijabe.20241704.8693 Citation: Awaafo A, Awafo Edward A., Mahdavi M, Vera D, Akolgo G A, Amankwah E, et al. Effects of crop residues for animal consumption and soil enhancement on the electricity generation potential of residues: A case study of Sawla-Tuna-Kalba district, Ghana. Int J Agric & Biol Eng, 2024; 17(4): 276–287.